Effect of Tube Expansion on Heat Transfer and Pressure Drop Characteristics During Condensation in Micro-Fin Tubes - Liu, Na; Zhao, Qian; Lan, Zhixiang (Frontiers in Energy Research, 2021)
Despite of the large number of research dedicated to condensation heat transfer and pressure drop characteristics in pristine micro-fin tubes, experimental investigation on effects of tube expansion have not been reported in the open literature. The paper reports measured cross-sectional dimensions, condensation heat transfer and pressure drop data of R1234ze(E) in pristine (5.10 mm OD) and expanded (5.26 mm OD) micro-fin tubes with mass fluxes from 100 to 300 kg/(m2·s). Effects of mass flux, vapor quality and tube expansion on the heat transfer coefficients and friction pressure gradients were investigated in the study. When the mass flux is 100 kg/(m2·s), the heat transfer coefficient and pressure drop of R1234ze(E) decrease after tube expansion. However, when the mass fluxes are 200 and 300 kg/(m2·s), tube expansion effects on the heat transfer coefficient and pressure drop are not notable. In addition, the experimental results are analyzed based on the existing condensation heat transfer and pressure drop correlations.